Los participios ribagorzanos en -áu, -éu, -íu - Terrado Pablo, Javier (Caplletra. Revista Internacional de Filologia, 2002)
This paper deals with a very specific problem: the Ribagorzan participles in -áu, -éu, -íu, which had so far been interpreted as castilianisms. It suggests that they could be genuine forms resulting from the vowelization of voiced dental consonants from Latin -D-, which has been documented in medieval Ribagorzan speech, or from the final dental consonant from Latin -T-; besides, this does not seem to be a recent solution.